2007
DOI: 10.3200/jexe.75.3.167-202
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Factors Influencing Teaching as a Career Choice: Development and Validation of the FIT-Choice Scale

Abstract: The authors apply current influential models from the motivational literature to develop the comprehensive factors influencing teaching choice (FIT-Choice) scale, to measure factors influencing the choice to teach for beginning preservice teacher education candidates. They validate the scale using 2 large cohorts (N = 488; 652) and describe the factors that teacher education candidates identified as most important in their decision to teach. Furthermore, the authors examine longitudinal relationships for parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
660
5
118

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 721 publications
(892 citation statements)
references
References 51 publications
48
660
5
118
Order By: Relevance
“…The analysis of candidates' responses to these essay questions quickly revealed that many of our teacher candidates hold beliefs that are consistent with the extant literature on why teachers choose a career in teaching (Book & Freeman,1986;Brookhart & Freeman, 1992;Goodlad, 1984;Joseph & Green, 1986;Serow, Eaker, & Ciechalski, 1992;Watt & Richardson, 2007). While the data from prior studies have typically not been analyzed in explicitly moral terms, we find that the most prominent reasons for becoming a teacher are significantly connected to the moral work of teaching.…”
Section: Primary Reasons For Choosing a Career In Teachingmentioning
confidence: 76%
“…The analysis of candidates' responses to these essay questions quickly revealed that many of our teacher candidates hold beliefs that are consistent with the extant literature on why teachers choose a career in teaching (Book & Freeman,1986;Brookhart & Freeman, 1992;Goodlad, 1984;Joseph & Green, 1986;Serow, Eaker, & Ciechalski, 1992;Watt & Richardson, 2007). While the data from prior studies have typically not been analyzed in explicitly moral terms, we find that the most prominent reasons for becoming a teacher are significantly connected to the moral work of teaching.…”
Section: Primary Reasons For Choosing a Career In Teachingmentioning
confidence: 76%
“…While it is agreed that there may be differences among the traditional and non-traditional respondents, both types of entrants into the field do express the welfare of children as a common motivation (Korthagen, 2004;Lee, 2010). Research has also found that preservice teachers, regardless of age, report altruistic reasons for pursuing a teaching career and appreciate the intrinsic value of teaching (Pop & Turner, 2009;Watt & Richardson, 2007).…”
Section: Limitationsmentioning
confidence: 99%
“…So far, existing research in the field suggests that this might be detrimental to producing teachers who are fully committed to the profession (e.g. Watt & Richardson, 2007).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The FIT-Choice (Factors Influencing Teaching Choice) scale assesses the primary motivations of teachers to teach, and was demonstrated to be psychometrically sound (see Watt & Richardson, 2007 for details). Students from universities of applied sciences are excluded, because 50.5 % of these students have restricted higher education entrance qualifications ('fachgebundene' and 'Fachhochschulreife').…”
Section: Data To Analyze Characteristics Of Applicants To the Professionmentioning
confidence: 99%
See 1 more Smart Citation